PERSEPSI BUNYI HENTIAN BERSUARA BAHASA INDONESIA OLEH PEMELAJAR TAIWAN - Johny Lee (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2020)
Abstract: This study investigated the perception performance of the voiced stops of Indonesian language by Taiwanese learners. Previous studies suggest that the perception of foreign languages’ phonemic category absent in the L1 inventory is troublesome, and this is also the case for the Taiwanese learners’ of Indonesian. Seven of eight of our subjects were unable yet to perfectly distinguish between the voiced stops [b, d, g] and their voiceless counterpart [p, t, k] despite being able to speak Taiwanese (Southern Min) which has the voicing distinction for bilabial stops [b]-[p] and velar stops [g]-[k]. The result yielded from a small sized experimental study of forced option test and literature study provides us a preliminary understanding on why some Taiwanese learners sometimes made production errors, oral and written. This study serves as a preliminary study which we hope to lead to a bigger-scale and well-controlled psychoacoustics study in the future in order to have a more definitive result on the perceptional issue by Taiwanese learners of Indonesian. Abstrak: Studi ini meneliti kemampuan persepsi pemelajar Taiwan terhadap bunyi konsonan hentian bersuara bahasa Indonesia. Penelitian sebelumnya menunjukkan bahwa pemelajar bahasa asing memiliki kesulitan mempersepsi terhadap bunyi-bunyi bahasa asing yang tidak dimiliki oleh kategori fonem bahasa pertama dan kondisi yang sama juga dijumpai pada pemelajar bahasa Indonesia sebagai bahasa asing asal Taiwan. Tujuh dari delapan subjek penelitian masih belum mampu untuk secara sempurna membedakan konsonan hentian bersuara [b, d, g] dan pasangan takbersuaranya [p, t, k] meski semua subjek mampu berbahasa Taiwan (Min Selatan) yang memiliki pembedaan ciri suara pada konsonan hentian bilabial [b]-[p] dan bunyi konsonan hentian velar [g]-[k]. Hasil yang dihasilkan dari penelitian eksperimen dengan teknik force option test dan rujukan kepustakaan berskala kecil ini memberikan gambaran awal tentang kemungkinan penyebab pemelajar bahasa Indonesia asal Taiwan terkadang membuat kekeliruan produksi bahasa, baik secara lisan maupun tulisan. Penelitian ini berfungsi sebagai studi awal yang diharapkan bisa diteruskan untuk penelitian berskala besar dan menggunakan metode psikoakustik untuk mendapatkan hasil yang lebih definitif terhadap isu persepsi pemelajar bahasa Indonesia asal Taiwan.